Teaching hands-on geophysics: examples from the Rū seismic network in New Zealand. (16th January 2017) - van Wijk, Kasper; Simpson, Jonathan; Adam, Ludmila
Abstract: Education in physics and geosciences can be effectively illustrated by the analysis of earthquakes and the subsequent propagation of seismic waves in the Earth. Educational seismology has matured to a level where both the hard- and software are robust and user friendly. This has resulted in successful implementation of educational networks around the world. Seismic data recorded by students are of such quality that these can be used in classic earthquake location exercises, for example. But even ocean waves weakly coupled into the Earth's crust can now be recorded on educational seismometers. These signals are not just noise, but form the basis of more recent developments in seismology, such as seismic interferometry, where seismic waves generated by ocean waves—instead of earthquakes—can be used to infer information about the Earth's interior. Here, we introduce an earthquake location exercise and an analysis of ambient seismic noise, and present examples. Data are provided, and all needed software is freely available.